(untitled) (Libyan Journal of Ecological & Environmental Sciences and Technology, 2019)
The effects of the aqueous extracts of aerial parts of mastic shrub (Pistacia lentiscus L.) at different concentrations (20, 40, 80%) were evaluated on germination and seedling growth of (Radish) Raphanus sativus L. and (Fenugreek) Trigonella foenum-graecum after 7 days in "in vitro condition ". Pistacia had strong allelopathic effects, it reduced the germination and seedling growth of Radish and Fenugreek, in all tested concentrations. Results obtained showed significant inhibition in germination percentage (GP), plumule length (PL) and radicle length (RL) of both Radish and Fenugreek seeds, and the degree of inhibition was in concentration dependent. At 20,40 and 80% Pistacia lentiscus L aqueous extracts the germination percentage of Radish seed was reduced to (81.67, 71.67 and 55%) respectively, while the germination of Fenugreek seeds was reduced to (75, 56.67 and 45%) respectively, comparative to control which was 100% and 98.3% for Radish and Fenugreek respectively.